Effect of compressed breast thickness on average glandular dose (AGD) during screening mammography using full-field digital mammography (FFDM) / Nur Izzati Najwa Suliman, Rafidah Supar and Hairenanorashikin Sharip - Suliman, Nur Izzati Najwa; Supar, Rafidah; Sharip, Hairenanorashikin (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Application of compression during mammography is crucial to reduce breast thickness and reducing average glandular dose (AGD). With increasing participation in regular breast screening programmes, the total AGD received by patient remains a concern. Therefore, this paper aimed to evaluate the effect of compressed breast thickness (CBT) on the AGD during screening mammography using full field digital mammogram (FFDM). This study involved retrospective collection of mammographic data and reports from 148 women who came for screening mammography. Mammographic parameters which include CBT, AGD, compression force and breast density for both breast on craniocaudal (CC) view and mediolateral oblique (MLO) view were recorded and analysed. There was statistically significant variation in the mammographic parameters value between CC and MLO projections but no significant variation between right and left breasts. For CC projection, a weak positive correlation was identified between CBT and AGD (r=0.115, p=0.049) and between CBT and compression force (r=0.172, p=0.003). In addition, a weak positive correlation was also found between CBT and compression force (r=0.200, p=0.001) and between CBT and AGD (r=0.292, p<0.001) in MLO projection. Reduction in CBTwas found to decrease AGD by approximately 0.007mGy/mm CBT. Adequate compression should be applied as it can reduce the CBT and consequently reduced the AGD to the patient.